Oxygen uptake in relation to body weight in a Hillstream fish Glyptothorax telchitta (Ham.) - Subba, Bharat Raj; Ghosh, Tapan Kumar (Nepalese Journal of Biosciences, 2013)
Oxygen uptake (VO2) through the gills of a hill-stream fish Glyptothorax telchitta from the Saptakoshi river (Nepal) has been studied in relation to different body weights. The oxygen uptake was determined at 24.0±1°C using a cylindrical glass respirometer with continuous water flow system. The aquatic oxygen uptake through the gills increased from 1.048 to 8.115 mlO2 kg-1.h-1 within the body weight range of 3.215 to 31.355 g. A fish of 17.052 g average body weight consumes 4.461 mlO2-1.h-1. The relation between oxygen uptake (VO2) and body weight was determined by performing regression analysis using logarithmic transformation. It has been found that with a unit increase in body weight, the oxygen uptake per unit time (mlO2h-1) increases by a power of 0.930 showing significant positive correlation whereas, the weight specific oxygen uptake decreases by a power of 0.070 showing significant but negative correlation. DOI: http://dx.doi.org/10.3126/njbs.v1i0.7464 Nepalese Journal of Biosciences 1: 11-18 (2011)